Framework to evaluate quality performance of green building delivery: construction and operational stage - Ayman M. Raouf (9908249) (2020)
Quality performance in construction is the degree of compliance with the specifications against which the work was executed. Green buildings extend the compliance to sustainability-related aspects to ensure that the energy and water consumption is conserved, promote a healthy indoor environmental quality and reducing the detrimental impacts of the construction activities on the environment. The operational stage reflects the construction workmanship and the effectiveness of the design solution to achieve the sustainability requirements through the overall building performance. Procedures for maintenance and overhauling extend the longevity of buildings. Green buildings exhibit underperformance caused by inadequate construction practices and a lack of understanding of the operations and maintenance practices. This research serves to tackle this problem through a comprehensive and forward-looking framework to depict construction- and operation-related quality activities through an integrated definition for the function modeling (IDEF0) process model. Semi-structured interviews and a focus group validate the framework’s suitability and its implementation offered revelations from industry practitioners on the factors affecting quality procedures from assigned metrics, liaison of staff from different project lifecycle stages, green building technologies, commissioning and retro-commissioning and impact of project delivery systems adopted especially in isolating operational liaison. The contributions of this work reinforce the impact of quality on the sustainability objectives that a green building is envisioned to serve, and through capturing the pre-, during, and post-construction lifecycle, the compliance and performance quality aspects are combined in a more integrated manner. Other Information Published in: International Journal of Construction Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/15623599.2020.1858539